2016
DOI: 10.1111/clr.12990
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue changes and crestal bone loss around platform‐switched implants placed at crestal and subcrestal levels: 36‐month results from a prospective split‐mouth clinical trial

Abstract: Up to 36 months of follow-up, soft tissue parameters and crestal bone levels can remain equally stable around dental implants placed at crestal and subcrestal levels. The need for long-term follow-up clinical trials is also emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
65
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 30 publications
(87 reference statements)
10
65
1
1
Order By: Relevance
“…On the contrary, some reports indicated that subcrestal implants showed no superiority against equicrestal implants with regard to the preservation of peri‐implant crestal bone levels . The findings of the present clinical trial are in line with the study conducted by Amri et al in which no statistically significant differences were found between crestal and subcrestal implants for the mean MBL changes at 6, 18, and 36 months. A recent systematic review and meta‐analysis reported that for bone level implants, the weighted mean of crestal bone loss before and after abutment connection was 0.03 ± 0.30 mm and 0.66 ± 0.11 mm when IAI placed subcrestally and 0.57 ± 0.29 mm and 0.80 ± 0.30 mm when IAI placed equicrestally .…”
Section: Discussionsupporting
confidence: 87%
“…On the contrary, some reports indicated that subcrestal implants showed no superiority against equicrestal implants with regard to the preservation of peri‐implant crestal bone levels . The findings of the present clinical trial are in line with the study conducted by Amri et al in which no statistically significant differences were found between crestal and subcrestal implants for the mean MBL changes at 6, 18, and 36 months. A recent systematic review and meta‐analysis reported that for bone level implants, the weighted mean of crestal bone loss before and after abutment connection was 0.03 ± 0.30 mm and 0.66 ± 0.11 mm when IAI placed subcrestally and 0.57 ± 0.29 mm and 0.80 ± 0.30 mm when IAI placed equicrestally .…”
Section: Discussionsupporting
confidence: 87%
“…Our current mesial and distal radiographic bone‐to‐implant contact in control group ‐0.21 mm was similar to the earlier studies, and lesser than the data published earlier . Meanwhile, the mesial and distal radiographic bone‐to‐implant contact in test group −0.32 mm was greater than the earlier studies on this technique, similar to the radiographic bone‐to‐implant contact −0.30 mm than the implant placed 2 mm subcrestally and also lesser than the bone‐to‐implant contact of −0.74 mm published earlier by Huang …”
Section: Discussionsupporting
confidence: 86%
“…The buccal mucosal recession in the present study was 0 mm and −0.02 mm for test and control groups, respectively and were slightly less than the buccal mucosa recession of −0.09 mm in earlier study on this technique . The range of mesial and distal radiographic bone‐to‐implant contact in other studies was −0.20, −0.24, −0.30, and −0.74 mm . Our current mesial and distal radiographic bone‐to‐implant contact in control group ‐0.21 mm was similar to the earlier studies, and lesser than the data published earlier .…”
Section: Discussionsupporting
confidence: 84%
“…Peri‐implant probing depth (PPD) was measured as described elsewhere; and digital bitewing radiographs (Ektaspeed plus; Kodak, Rochester, New York) were taken and viewed on a calibrated computer screen (Samsung SyncMaster digital TV monitor, Suwon City, Gyeonggi‐do, Korea). CBL was measured as the linear distance from 2 mm below the implant‐abutment interface to the most crestal part of the alveolar bone . Peri‐implantitis was defined as the presence of at least 1 peri‐implant site with a PPD of ≥ 4 mm; and radiographic mesial or distal CBL of ≥3 mm around the implant .…”
Section: Methodsmentioning
confidence: 99%